2016
DOI: 10.1002/ajhb.22845
|View full text |Cite
|
Sign up to set email alerts
|

A three‐dimensional geometric morphometrics view of the cranial shape variation and population history in the New World

Abstract: The three approaches used in this study highlight the importance of local processes especially in Baja California, and caution against the use of overly simplistic models when searching for the number of migration events. The results stress the complexity of the settlement of the Americas as well as the mosaic nature of the processes involved in this process. Am. J. Hum. Biol. 28:646-661, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 105 publications
(204 reference statements)
4
17
0
6
Order By: Relevance
“…Another possibility may be the application of landmark-based geometric morphometrics. This approach has been extensively used in anthropology to assess sexual dimorphism on 3D models of crania, coxal bones and femora (Hennessy et al 2005;Bilfeld et al 2012Bilfeld et al , 2013Franklin et al 2012;Morgan et al 2013;Cho et al 2015;Cavaignac et al 2016;Chovalopoulou et al 2016;Duquesnel Mana et al 2016) to investigate population variation (Hennessy & Stringer, 2002;Cho et al 2015;Galland & Friess, 2016;Lesciotto et al 2016) but not yet to estimate age-at-death.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Another possibility may be the application of landmark-based geometric morphometrics. This approach has been extensively used in anthropology to assess sexual dimorphism on 3D models of crania, coxal bones and femora (Hennessy et al 2005;Bilfeld et al 2012Bilfeld et al , 2013Franklin et al 2012;Morgan et al 2013;Cho et al 2015;Cavaignac et al 2016;Chovalopoulou et al 2016;Duquesnel Mana et al 2016) to investigate population variation (Hennessy & Stringer, 2002;Cho et al 2015;Galland & Friess, 2016;Lesciotto et al 2016) but not yet to estimate age-at-death.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…In this way, it contributed to the emergence of many Native North American groups (Raghavan et al, ). Several craniometric studies reported that modern and palaeoamerical data corresponds with multiply population events of the America, with the more recent circumarctic gene flow facilitating the dispersion of northeast Asian‐derived characters among the North Americans (de Azevedo et al, ; Galland & Friess, ; González‐José, Bortolini, Santos, & Bonatto, ).…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos aqui citados indicam que sinais de seleção natural em partes do crânio de populações árticas são a razão de sua distinção morfológica em relação ao restante dos nativos americanos. Além disso, há a possibilidade de que deriva genética esteja atuando em populações isoladas, como os pericues, no Novo México, mostrando que múltiplas forças podem ter influenciado na variação morfológica nas Américas (Galland;Friess, 2016). Os pesquisadores que estudam crânios para inferir padrões de movimentação populacional argumentam que, ainda que seja notável a ação de fatores ambientais em algumas partes da morfologia craniana, tais como o módulo mastigatório, o crânio como um todo ainda reflete a divergência histórico-genética, já que seus módulos variam de forma correlacionada, fenômeno esse chamado de integração morfológica (González-José et al, 2004).…”
Section: Número De Migrações Para As Américasunclassified
“…Já entre os morfologistas, alguns acreditam no MDCBP, que propõe a entrada de duas levas biológicas principais para as Américas Hubbe, 2005), enquanto outros buscam compatibilizar a variação craniométrica no continente com o modelo genético, propondo uma entrada única composta por uma população altamente variável (González-José et al, 2008;De Azevedo et al, 2011 ou por uma população que tenha se modificado 8 Ver Malaspinas et al (2014), para extração de DNA autossômico. in situ por fatores ambientais Monteiro, 2009;Perez et al, 2011;Menéndez et al, 2014) ou estocásticos (Galland;Friess, 2016). Por fim, pesquisas sobre o modo de vida das primeiras populações americanas ainda têm sofrido com a escassez de dados e a complexidade das interações entre humanos e ambiente.…”
Section: Discussão E Conclusõesunclassified